2020
DOI: 10.1017/qua.2019.85
|View full text |Cite
|
Sign up to set email alerts
|

Millennial-scale increase in winter precipitation in the southern Rocky Mountains during the Common Era

Abstract: We employed the modern analog technique to quantitatively reconstruct temperature and precipitation over the past 2500 yr based on fossil pollen records from six high-elevation lakes in northern Colorado. Reconstructed annual temperatures for the study area did not deviate significantly from modern over the past 2500 yr despite hemispheric expressions of Medieval Climate Anomaly warmth and Little Ice Age cooling. Annual precipitation, however, shifted from lower than modern rates from 2500 to 1000 cal yr BP to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 62 publications
(147 reference statements)
0
9
0
Order By: Relevance
“… ( A ) 45°N June insolation ( 54 ); ( B ) Jenny Lake total organic carbon (TOC) flux ( 16 ); ( C ) Jenny Lake BSi flux ( 16 ); ( D ) median lake level (with ±1 SD as gray error envelope) reconstructed from five lakes in Wyoming and Colorado (table S3) ( 25 ); ( E ) sediment carbonate oxygen isotope (δ 18 O) (per mil, ‰) record from Bison Lake, Colorado, as a proxy for variations in the seasonality of precipitation ( 37 ); ( F ) winter precipitation anomaly reconstructed from six high-elevation lakes in the Park Range, northern Colorado ( 44 ); and ( G ) glacier-derived clastic sediment flux at Delta Lake (this study). Heavy black lines are LOESS functions in (B), (C), (E), (F), and (G).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… ( A ) 45°N June insolation ( 54 ); ( B ) Jenny Lake total organic carbon (TOC) flux ( 16 ); ( C ) Jenny Lake BSi flux ( 16 ); ( D ) median lake level (with ±1 SD as gray error envelope) reconstructed from five lakes in Wyoming and Colorado (table S3) ( 25 ); ( E ) sediment carbonate oxygen isotope (δ 18 O) (per mil, ‰) record from Bison Lake, Colorado, as a proxy for variations in the seasonality of precipitation ( 37 ); ( F ) winter precipitation anomaly reconstructed from six high-elevation lakes in the Park Range, northern Colorado ( 44 ); and ( G ) glacier-derived clastic sediment flux at Delta Lake (this study). Heavy black lines are LOESS functions in (B), (C), (E), (F), and (G).…”
Section: Discussionmentioning
confidence: 99%
“…For example, multiproxy data from Crevice Lake in northern Yellowstone National Park suggest a period of extreme drought between 2.2 and 0.8 ka ( 43 ), and a trend of reduced snowfall from 2.4 to 1.0 ka followed by increased snowfall during the past millennium is indicated by a quantitative reconstruction of winter precipitation from a series of small high-elevation lakes in the Park Range, northern Colorado ( Fig. 4F ) ( 44 ). This pattern is also supported by stratigraphic evidence for the timing of Holocene highstands beginning after 1.0 ka in similar high-elevation lakes in the area ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This does not preclude the importance of climate in driving fire activity at larger landscape to regional scales, as documented in several fire history studies in Western North America (Calder et al, 2015; Kelly et al, 2013; Marlon et al, 2012; Schoennagel et al, 2004, 2007; Sibold and Veblen, 2006; Whitlock et al, 2003). Second, pollen-based temperature reconstructions from the Park Range of northern Colorado do not appear to have the signature of either the high temperatures of the Medieval Climate Anomaly or the low temperatures of the Little Ice Age (Parish et al, 2020), thus making temperature an unlikely driver of the changes observed in this record. Previous work has also shown that the spatial variations in these climatic changes may not have included the temperature anomalies seen elsewhere to southwestern North America and the southern Rocky Mountains (Neukom et al, 2019; Viau et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we compared the Chickaree Lake pollen record to regional climate reconstructions to evaluate the influence of millennial-scale climate changes on the vegetation and fire activity. Because pollen-based paleoclimate reconstructions from the region did not show evidence of changes in mean annual or seasonal temperature over the past 2000 year (Parish et al, 2020), we focused on precipitation-based paleoclimate reconstructions. We visually compared the millennial-scale changes in pollen observed at Chickaree Lake, as captured by NMDS axis 1, to lake level, δ 18 O, and pollen-based precipitation reconstructions from other studies within the region (Anderson et al, 2015; Parish et al, 2020; Shuman et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation